Cancer risk in patients with bipolar disorder and unaffected siblings of such patients: A nationwide population‐based study. Issue 10 (10th January 2022) - Chen, Mu‐Hong; Tsai, Shih‐Jen; Su, Tung‐Ping; Li, Cheng‐Ta; Lin, Wei‐Chen; Cheng, Chih‐Ming; Chen, Tzeng‐Ji; Bai, Ya‐Mei
Abstract: Increasing evidence suggests that patients with bipolar disorder are more likely to develop malignant cancer than in the general population. However, the overall cancer risk in the unaffected siblings of such patients remains unknown. From the National Health Insurance Research Database of Taiwan, 25 356 patients with bipolar disorder, 25 356 age‐matched unaffected siblings of patients with bipolar disorder and 101 422 age‐matched controls without severe mental disorders between 1996 and 2010 were enrolled in our study. Patients who developed cancer between the time of enrollment and the end of 2011 were identified. Cancers were divided into three subgroups based on the related layer of embryonic development: ectodermal, mesodermal and endodermal cancers. Patients with bipolar disorder (odds ratio [ OR ] = 1.22, 95% confidence interval [CI]: [1.06, 1.40]) and unaffected siblings of such patients ( OR  = 1.17, 95% CI [1.02, 1.34]) had greater risk of developing malignant cancer than did controls. Furthermore, only those aged <50 years, for both patients with bipolar disorder ( OR  = 1.90, 95% CI [1.38, 2.61]) and unaffected siblings ( OR  = 1.65, 95% CI [1.19, 2.28]), were more likely to develop the ectodermal cancer, especially breast cancer, than the control group. The associations of bipolar disorder and susceptibility to bipolar disorder with increased cancer risk in the younger population may imply a genetic overlap in neurodevelopment and malignancy pathogenesis. Our findings may encourage clinicians to monitor cancer risk factors and warning signs closely in patients with bipolar disorder and unaffected siblings of such patients. Abstract : What's new? Increasing evidence suggests that patients with bipolar disorder are more likely to develop malignant cancer than the general population. However, the overall cancer risk in the unaffected siblings of such patients remains unknown. This study found that patients with bipolar disorder and their unaffected siblings were more likely to develop cancer than controls without severe mental disorders. Furthermore, only participants aged <50 were more likely to develop ectodermal cancers. The findings imply a genetic overlap in neurodevelopment and malignancy pathogenesis and may encourage clinicians to closely monitor patients with bipolar disorder and their unaffected siblings for cancer warning signs.